PENEGAKAN HUKUM BAGI PELAKU TINDAK PIDANA PENCABULAN TERHADAP ANAK (Studi Kasus Kepolisian Daerah Bali) - Ni Ketut Sri Ratmini; I Made Adi Widnyana; I Gusti Ayu Agung Shaskara Bhakti Paramesty; Dewi bunga; Dewa Putu Tagel (VYAVAHARA DUTA, 2024)
Children are part of the younger generation who are the successors of the ideals of the nation's struggle as well as human resources for the development of the country in the future. Laws are made with the aim of regulating and maintaining order, justice so that chaos in society can be controlled or prevented. The purpose of this study was carried out to determine the form of sanctions given to perpetrators of Criminal Acts of Obscenity against and the efforts of the Bali Regional Police in Law Enforcement for Perpetrators of Criminal Acts of Sexual Abuse against children. This research refers to several relevant literature and concepts as a reference source. The theory used to analyze the problem formulation is: Soerjono Soekanto's Law Enforcement Concept. The research methods used in this study are empirical research types, descriptive research properties, qualitative data forms, primary and secondary data sources, data collection using interview methods, literature studies, determination of research informants using non-probality sampling techniques, research instruments using mobile phones and recording. The data analysis used is descriptive qualitative. The results of the research obtained are as follows: 1) The forms of sanctions for perpetrators of child molestation crimes are as follows: principal and additional crimes, fines and cover-up crimes. 2) the Bali Regional Police has 2 Law Enforcement efforts for Perpetrators of Child Abuse Crimes, among others, preventive and repressive efforts